Disabling Consent, or Reconstructing Sexual Autonomy - Fischel, Joseph J.; O'Connell, Hilary R. (Columbia Journal of Gender and Law, 2015)
Does a right to sexual autonomy criminalize the embellished pick-up line? Or does a right to sexual autonomy permit each and every consensual sex act, however life- threatening, or even life-ending? This Article defends (by reconstructing) sexual autonomy as the governing principle of modern rape law. Powerful criticisms of sexual autonomy otherwise normatively opposed share an antecedent assumption: that sexual autonomy can be read off and as first person present active (or passive) consent (Part I). This Article argues against the conflation of sexual autonomy with sexual consent. Instead, and in conversation with competing liberal and feminist political theoretic accounts of sexual autonomy, this Article defines sexual autonomy as the capability to codetermine sexual relations (Part II). By interfacing a revised concept of sexual autonomy against and alongside State v. Fourtin, a 2012 Connecticut Supreme Court decision overturning a conviction of sexual assault against a severely mentally and physically disabled woman (Part III), the Article proposes three possibilities for statutory reform: refurbishing consent; expanding restrictions on status relations; and applying an accommodation model of disability entitlements to sexual relations (Part IV). After synopsizing our interventions, the Conclusion reminds readers that our brief for sexual autonomy, relationally reconstructed, presumes and propounds the ordinariness, not the extraordinariness, of sex.